An excellent thermostable dual-functionalized 3D fsx-type Cd(ii) MOF for the highly selective detection of Fe3+ ions and ten nitroaromatic explosives. Issue 35 (13th August 2021) - Wen, Gui-Lin; Wu, Wei-Ping; Wang, Feng-Wu; Liu, Dao-Fu; Wang, Xiao-Ling; Rong, Jie-Wei; Wang, Yao-Yu
Abstract : A 3D fsx -type thermostable MOF was designed and synthesized for the highly selective detection of Fe 3+ ions and ten nitroaromatic explosives. Abstract : Suitable chemical components in water systems for human health are a crucial prerequisite for mankind's survival. Simple and effective innovations are being developed to efficiently monitor healthy and toxic substances. Here, with a hydrothermal technique, a novel thermostable metal–organic framework (MOF) [Cd2 (L)(bib)0.5 (H2 O)3 ] n ·1.75 n (H2 O) (MOF-1, H4 L = biphenyl-2, 3, 3′, 5′-tetracarboxylic acid, bib = 1, 4-bis(imidazolyl)butane) was designed and synthesized. MOF-1 shows a 4, 5-connection binodal 3D fsx -type topological net with irregular cages, which the bulk materials show high phase purity, excellent thermo/aqua-stability and intense fluorescence. The luminescent MOF was studied for the highly sensitive detection of trace amounts of Fe 3+ ions and nitrobenzene and shows high K SV values of 4.653 × 10 4 and 5.724 × 10 4, respectively. It was also demonstrated that MOF-1 possesses superior probing ability towards nine other nitroaromatic explosives with remarkable quenching percentages. These results offer a new possibility for the potential multiple recognition of various chemical substances in human body and water systems by utilizing novel dual-functionalized luminescent MOF sensors.